THE INFLUENCE OF USING INSTAGRAM MEDIA @PESONA.INDONESIA ON FULFILLING THE INFORMATION NEEDS OF FOLLOWERS - Sidik, Jafar; Andrini, Susi (Transpublika Publisher, 2024)
Instagram media is a media that plays a very important role in the lives of today's young generation. The use of social media as a provider of information needs can be seen from the Instagram account. One piece of information that is very important is information regarding local tourism aspects. One account that utilizes and is related to local tourist information is @Pesona.indonesia. The aim of this research is a). to find out whether there is an influence of using Instagram @pesona.indonesia on meeting the information needs of followers. and b). to find out how much influence the use of social media Instagram @pesona.indonesia has on fulfilling the information needs of its followers. This research uses an explanatory quantitative method, namely research that aims to explain the relationship of a variable with other variables to test a hypothesis. The population in this study used the Slovin formula which took samples from followers on the Instagram account @Pesona.indonesia, with a sample of one hundred respondents at a ten percent error rate. The questionnaire was distributed via Google Form and processed using SPSS version twenty-nine. The results of this research show that there is an influence of the use of social media Instagram which has a very strong influence on information needs. While the rest is influenced by other factors outside this research.